2017
DOI: 10.1016/j.archoralbio.2017.07.024
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for sex estimation using 3D computed tomography models of tooth roots: A volumetric analysis

Abstract: Advances in technologies such as computed tomography (CT) scanning have allowed for further examination of dental sexual dimorphism in modern and archaeological populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 45 publications
(70 reference statements)
0
17
3
Order By: Relevance
“…In the current study, significant dimorphism in root volume was found for all tooth types (upper central incisor, upper lateral premolar, lower canine and lower lateral premolar). Kazzazi and Kranioti (2017) suggest that their results demonstrate the potential of tooth root volume measurements for sex assessment in archaeological samples. They also recommend the incorporation of more archaeological samples and contemporary populations due to the small sample size of the original study.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In the current study, significant dimorphism in root volume was found for all tooth types (upper central incisor, upper lateral premolar, lower canine and lower lateral premolar). Kazzazi and Kranioti (2017) suggest that their results demonstrate the potential of tooth root volume measurements for sex assessment in archaeological samples. They also recommend the incorporation of more archaeological samples and contemporary populations due to the small sample size of the original study.…”
Section: Discussionmentioning
confidence: 68%
“…A similar pattern has been observed in previous studies; males have a greater dentine component and females have thicker enamel (Stroud et al, 1994; Schwartz and Dean, 2005; Smith et al, 2006; Saunders et al, 2007; Feeney et al, 2010; García-Campos et al, 2018a; b). A study of an Iranian archaeological sample found significant sexual dimorphism in the root volume of all teeth (Kazzazi and Kranioti, 2017). In the current study, significant dimorphism in root volume was found for all tooth types (upper central incisor, upper lateral premolar, lower canine and lower lateral premolar).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of other dental measurements, such as tissue volumes, has been less common than traditional crown diameters, but dental tissue proportions, tissue volumes, and surface areas have also been identified as being sexually dimorphic (Feeney et al, 2010; García‐Campos, Martinón‐Torres, Martínez de Pinillos, et al, 2018; García‐Campos, Martinón‐Torres, Martín‐Francés, et al, 2018; Harris & Hicks, 1998; Kazzazi & Kranioti, 2017; Saunders, Chan, Kahlon, Kluge, & FitzGerald, 2007; Schwartz & Dean, 2005; Sorenti, Martinón‐Torres, Martín‐Francés, & Perea‐Pérez, 2019; Stroud, Buschang, & Goaz, 1994; Tardivo et al, 2011; Tardivo et al, 2015; Zilberman & Smith, 2001). Despite being used infrequently, the use of dental tissue volumes and surface areas has been recommended for sex determination (García‐Campos, Martinón‐Torres, Martín‐Francés, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 60 years, following the study of Hunt Jr and Gleiser (1955) about sex estimation from osseous and dental remains of nonadult individuals, analyses have been carried out to determine a reliable method for sex estimation from teeth. Thus, numerous studies have quantified sexually dimorphic differences between males and females through odontometric techniques, with the demonstration that sexual dimorphism results in larger teeth in males than females in permanent dentition (Adams & Pilloud, 2019; Angadi, Hemani, Prabhu, & Acharya, 2013; Capitaneanu, Willems, Jacobs, Fieuws, & Thevissen, 2017; Hassett, 2011; Kazzazi & Kranioti, 2017, 2018; Khamis, Taylor, Malik, & Townsend, 2014; Luna, 2019; Peckmann, Logar, Garrido‐Varas, Meek, & Pinto, 2016; Peckmann, Meek, Dilkie, & Mussett, 2015; Shaweesh, 2017; Sonika, Harshaminder, Madhushankari, & Sri Kennath, 2011; Tardivo et al, 2015; Viciano, Alemán, D'Anastasio, Capasso, & Botella, 2011; Viciano, D'Anastasio, & Capasso, 2015; Viciano, López‐Lázaro, & Alemán, 2013; Yong et al, 2018; Zorba, Moraitis, Eliopoulos, & Spiliopoulou, 2012; Zorba, Moraitis, & Manolis, 2011; Zorba, Vanna, & Moraitis, 2014) and deciduous teeth (López‐Lázaro, Alemán, Viciano, Irurita, & Botella, 2018; Paknahad, Vossoughi, & Ahmadi Zeydabadi, 2016; Shankar et al, 2013; Singh, Bhatia, Sood, & Sharma, 2017; Viciano et al, 2013; Żądzińska, Karasińska, Jedrychowska‐Dańska, Watala, & Witas, 2008).…”
Section: Introductionmentioning
confidence: 99%